A simplified Nonlinear Sway-Rocking model for evaluation of seismic response of structures on shallow foundations. Issue 81 (February 2016) - Lu, Yang; Marshall, Alec M.; Hajirasouliha, Iman
Abstract: This paper presents a simplified Nonlinear Sway-Rocking model as a preliminary design tool for seismic soil-structure interaction analysis. The proposed model is intended to capture the nonlinear load-displacement response of shallow foundations during strong earthquake events where foundation bearing capacity is fully mobilised. Emphasis is given to heavily-loaded structures resting on a saturated clay half-space. The variation of soil stiffness and strength with depth, referred to as soil non-homogeneity, is considered in the model. Although independent springs are utilised for each of the swaying and rocking motions, coupling between these motions is taken into account by expressing the load-displacement relations as functions of the factor of safety against vertical bearing capacity failure ( FSv ) and the moment-to-shear ratio ( M / H ). The simplified model has been calibrated and validated against results from a series of static push-over and dynamic analyses performed using a more rigorous finite-difference numerical model. Despite some limitations of the current implementation, the concept of this model gives engineers more degrees of freedom in defining their own model components, providing a good balance between simplicity, flexibility and accuracy. Highlights: A simplified model is developed to capture nonlinear seismic foundation response. The effects of soil nonlinearity and heterogeneity are accounted for in the model. A unique dimensionless backbone is employed for each of sway and rocking motions. The FLAC 3D numerical code is used to calibrate and validate the simplified model.